The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1179/136485905x24210
|View full text |Cite
|
Sign up to set email alerts
|

Cytotaxonomic description ofSimulium kaffaense, a new member of theS. damnosumcomplex (Diptera: Simuliidae) from south–western Ethiopia

Abstract: Although Ethiopia is one of the countries worst affected by human onchocerciasis, the exact taxonomic identity of the blackflies acting as the main vectors in the endemic areas has never been determined. A cytotaxonomic analysis of Simulium damnosum s.l. collected from three endemic sites in south-western Ethiopia has now revealed the existence of the 'Kisiwani' form (a non-anthropophilic cytoform that is common in East Africa) and a newly recognized species, Simulium kaffaense. Simulium kaffaense sp. nov. is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…cytoform ('Olifants') has been described from north-western South Africa (Krü ger et al, 2005) but this form could not be found among the specimens collected in 1981. The present results confirm the occurrence of two distinct cytoforms in southwestern Ethiopia, which are related to the 'Kisiwani' form (Dunbar and Vajime, 1972) and S. kaffaense (previously known as the 'Jimma' cytoform; Dunbar and Vajime, 1981;Hadis et al, 2005). The results include the first records for Ilubabor province, all previous studies on S. damnosum s.l.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…cytoform ('Olifants') has been described from north-western South Africa (Krü ger et al, 2005) but this form could not be found among the specimens collected in 1981. The present results confirm the occurrence of two distinct cytoforms in southwestern Ethiopia, which are related to the 'Kisiwani' form (Dunbar and Vajime, 1972) and S. kaffaense (previously known as the 'Jimma' cytoform; Dunbar and Vajime, 1981;Hadis et al, 2005). The results include the first records for Ilubabor province, all previous studies on S. damnosum s.l.…”
Section: Discussionsupporting
confidence: 88%
“…The distinction made between 'Kisiwani E' and its southern relatives needs confirmation, by the collection and examination of specimens from southern or central Ethiopia. The small sample size and the detection of a newly recognized inversion (2L-207) made it impossible to say whether the S. kaffaense identified in the present study were identical with one of the two cytotypes identified by Hadis et al (2005) or whether they represented another distinct sub-population. The River-Sor specimens appeared to have a higher frequency of inversion 2L-13 (with two homozygotes for this inversion) than the specimens found in the other rivers, and included the only specimen found to have the 3L-8 inversion ( Table 2).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations